PENGELOLAAN POTENSI MINYAK ATSIRI DENGAN COLLABORATIVE GOVERNANCE SEBAGAI BENTUK PEMBANGUNAN EKONOMI KERAKYATAN BERKELANJUTAN PADA PROVINSI ACEH - Nanda Yuniza (Journal Education and Government Wiyata, 2024)
Essential oil is one of the export commodities that has high value. Aceh Province is one of the suppliers of essential oils to the world market, but the development of essential oil potential has not been carried out optimally due to ego sectoral factors, lack of coordination, lack of budget, lack of business development assistance and the absence of policies to support business development and lack of innovation. The purpose of this study is to build a collaboration strategy between agencies, academics and the community in managing essential oil potential so that the development of innovation and empowerment of essential oils in Aceh Province can be carried out optimally. This study was conducted using a qualitative approach, and analyzed in two stages using PETEL and SWOT analysis. The results of the study 1) the development of essential oil potential is carried out using analysis of political, economic, social, technological, environmental and legal factors. Based on the PETEL analysis, it was found that to develop essential oil potential, an active role of the government is needed through collaboration between related agencies and the community starting from the planning, implementation to evaluation stages with a commitment to the development of Aceh; 2) the results of the study using SWOT analysis obtained a strength-threat strategy, namely maximizing the use of potential to minimize threats. The method is to use Pancasila economics which is implemented with the contribution of all stakeholders, maximizing the role of the community, creating a design plan and collaborative governance.